Variation in Vessel Element Diameters and Densities Across Habitats at the Community and Species Levels in Southeast Florida - George King Rogers (Biology)
The study of woody dicot xylem structure in relation to habitats has a long but geographically incomplete history, generating generalizations and questions still in need of expanded data. One understudied area is localized cross-habitat studies under identical climate conditions. Also sparse are intraspecific cross-habitat data. Both of these weaknesses are addressed in the present project for unstudied S. Florida. Six surveys of woody dicot branchlet microtome cross-sections allowed the microscopic comparison of vessel element (VE) diameters and VE densities. The project took place in a small area within short timeframes per survey to assure near uniformity in weather and in seasonal growth cycles. The multispecies Initial Survey and single-species Ximenia americana Survey addressed the question of adjustments in VE diameters and/or VE densities in shaded vs. sunny habitats, finding significant downward average adjustment in VE densities in shaded hammock vs. open pineland habitats (112 shade vs. 182 VE/mm2 sun) but not in VE diameters. Single-species (Chrysobalanus icaco, Morella cerifera) surveys examined adjustments in VE diameters and VE densities in swamp vs. scrub (diameter mean: 42.5 µm swamp, 49.2 µm scrub; density means: 179.9 swamp, 154.0 scrub). Chrysobalanus icaco, having arguably the greatest environmental breadth and having the largest mean vessel element diameters in the project, was the sole species to adjust VE diameters only across habitats. Coefficients of variation in VE density exceeded those in VE diameters in every survey. This project sets the stage for future work in Florida and beyond aimed at isolation of environmental variables with respect to xylem traits and aimed at causal mechanisms, especially mode of xylem adjustment in relation to conductive risk.